2019
DOI: 10.1097/lbr.0000000000000493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Routine Clopidogrel Use on Bleeding Complications After Endobronchial Ultrasound-guided Fine Needle Aspiration

Abstract: We suggest that EBUS-TBNA, using 22 and 21-G needles, is safe with high yields in patients with mediastinal/hilar adenopathy, actively taking clopidogrel and aspirin, and are at high risk for thrombotic complications if the medication is discontinued.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The study by Webb et al 11 adds to the emerging data on EBUS-TBNA safety, reassuring us that, in the hands of expert bronchoscopists, this procedure can indeed be performed safely on patients receiving antiplatelet therapy. Although there is a collective lack of bleeding complications in all studies performed to date, we should still interpret these results with caution.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The study by Webb et al 11 adds to the emerging data on EBUS-TBNA safety, reassuring us that, in the hands of expert bronchoscopists, this procedure can indeed be performed safely on patients receiving antiplatelet therapy. Although there is a collective lack of bleeding complications in all studies performed to date, we should still interpret these results with caution.…”
mentioning
confidence: 93%
“…In the current issue of The Journal of Bronchology and Interventional Pulmonology, Webb et al 11 present their experience performing EBUS-TBNA on patients on both aspirin and clopidogrel. In this multicenter prospective study, the authors included all subjects presenting with mediastinal or hilar lymphadenopathy requiring sampling for staging and/or diagnosis.…”
mentioning
confidence: 99%
“…However, the management of ATAs before and after EBUS-TBNA has not yet been well understood. Several previous studies have shown that EBUS-TBNA could be performed safely in patients taking clopidogrel, but these studies were based on small numbers of cases [9][10][11].…”
Section: Introductionmentioning
confidence: 99%